Evolution of management of gout. Issue 2 (March 2015) - Khanna, Puja P.; FitzGerald, John
<x xml:space="preserve">Abstract</x> Purpose of review There have been several guidelines on the management of gout over the last decade; however, inconsistencies between them create confusion for practitioners. This review highlights areas of agreement between guidelines and discusses data where disagreements exist. Recent findings For acute gout, the guidelines agree that anti-inflammatory treatment should start as soon as possible, preferably within 24 hours. Older guidelines preferred NSAIDs or colchicine over steroids, but newer ones leave the choice of agent to the physician. For colchicine, all guidelines recommend using low dose. Intra-articular, oral or intramuscular steroids are all described as effective. For management of hyperuricemia, indications for initiating urate-lowering therapy (ULT) have become more inclusive over the years by requiring lower burden of disease severity or including patient comorbidities. Probenecid has fallen out of favour with most guidelines favouring allopurinol over febuxostat. Although there is a disagreement about timing of initiation for ULT, guidelines recommend treating to target of serum urate (sUA) less than 6 mg/dl, and less than 5 mg/dl for patients with more severe disease. Concurrent anti-inflammatory prophylaxis has gained strong support over the years. Summary Most guidelines are in agreement with recommendations for management of gout and most changes have been directional and evolutionary.